Pediatric Minimum Speech Test Battery. - Uhler, Kristin; Warner-Czyz, Andrea; Gifford, Rene (Journal of the American Academy of Audiology, 2017)
Background: Assessment of patient outcomes and documentation of treatment efficacy serves as an essential component of (re)habilitative audiology; however, no standardized protocol exists for the assessment of speech perception abilities for children with hearing loss. This presents a significant challenge in tracking performance of children who utilize various hearing technologies for within-subjects assessment, between-subjects assessment, and even across different facilities. Purpose: The adoption and adherence to a standardized assessment protocol could help facilitate continuity of care, assist in clinical decision making, allow clinicians and researchers to define benchmarks for an aggregate clinical population, and in time, aid with patient counseling regarding expectations and predictions regarding longitudinal outcomes. Design: The Pediatric Minimum Speech Test Battery (PMSTB) working group--comprised of clinicians, scientists, and industry representatives--commenced in 2012 and has worked collaboratively to construct the first PMSTB, which is described here. Conclusions: Implementation of the PMSTB in clinical practice and dissemination of associated data are both critical for achieving the next level of success for children with hearing loss and for elevating pediatric hearing health care ensuring evidence-based practice for (re)habilitative audiology.